2019
DOI: 10.1016/j.ijpharm.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vitamin C skin permeation from supramolecular hydrogels, illustrated using in situ ToF-SIMS 3D chemical profiling

Abstract: Vitamin C (ascorbic acid) is a naturally occurring, powerful anti-oxidant with the potential to deliver numerous benefits to the skin when applied topically. However, topical use of this compound is currently restricted by an instability in traditional formulations and the delivery and eventual fate of precursor compounds has been largely unexplored. Time of flight secondary ion mass spectrometry (ToF-SIMS) is an emerging technique in the field of skin research and offers detailed chemical analysis, with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Sequences characteristic to these proteins were manually assigned in situ in the skin layers where they are known to be present exclusively or predominantly. The layers of the skin in the depth profile, specifically the stratum corneum, underlying epidermis and dermis, were assigned based on the abundance of a phospholipid marker (PO 3 − ), as described in previous analysis of skin in SIMS by Starr et al 32 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Sequences characteristic to these proteins were manually assigned in situ in the skin layers where they are known to be present exclusively or predominantly. The layers of the skin in the depth profile, specifically the stratum corneum, underlying epidermis and dermis, were assigned based on the abundance of a phospholipid marker (PO 3 − ), as described in previous analysis of skin in SIMS by Starr et al 32 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Derivatives of Vit C, such as sodium ascorbyl phosphate, magnesium ascorbyl phosphate, sodium ascorbate and ascorbyl-6-palmitate have been employed in cosmetic and pharmaceutical formulations in order to remedy this problem [Segall and Moyano, 2008;Serrano et al, 2015]. However, despite being more stable, their permeation efficiencies and biological activities are still limited [Stamford, 2012;Starr et al, 2019;Caritá et al, 2020]. Results disclosed in patents also show limited stabilization effects of anhydrous formulations [Thomas, 2014].…”
Section: Chemical Stability Of Vit Cmentioning
confidence: 99%
“…Supramolecular hydrogels and their capability to enhance skin permeation of vitamin C (ascorbic acid) and its precursor (ascorbyl glucoside) have also been investigated with 3D-SIMS of ex vivo porcine skin [40]. Researchers demonstrated that the hydrogel enhances skin permeation of both compounds and preserves the conversion of the precursor into vitamin c until it reaches the epidermal layer, the intended target ( Fig.…”
Section: D Sims-msimentioning
confidence: 99%
“…The results showed a deeper permeation when a hydrogel is used. This article was published in[40] (copyright Elsevier). b Quantitative 3D MALDI-MSI of the anti-cancer drug paclitaxel in a malignant pleural mesothelioma tumor.…”
mentioning
confidence: 99%